Review: Li-Fi Future Technology, Architecture, and their Constraints (Texas Journal of Engineering and Technology, 2022)
Light Fidelity (Li-Fi) is a network and mobile communication system that uses light to transmit data at fast speeds in both directions. Li-Fi is a wireless network made up of multiple light bulbs that provides a user experience that is very similar to Wi-Fi except that it uses the spectrum of light. Li-Fi is a type of Visible Light Communication (VLC) that uses light as a communication medium instead of wires. Li-Fi hasrecently advanced to address the disadvantages of Wi-Fi. This paper can be used as a reference and source of information for developing Li-Fi technology, it provides an overview of Li-Fi, covering the architecture of Li-Fi and its application environment, the differences between Wi-Fi and Li-Fi technologies, and the limitations of Li-Fi technology based on a review of numerous Li-Fi technology studies, as well as a brief discussion of Li-Fi efficiency and availability.